2013
DOI: 10.1021/jz401636s
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of Single-Crystal ZnO by a Conjugated Polyelectrolyte Designed to Avoid Aggregation

Abstract: A conjugated polyelectrolyte (CPE) based on a poly(phenylene ethynylene) backbone designed to avoid interchain aggregation was adsorbed onto n-type zinc oxide (0001) single crystals. Photophysical, atomic force microscopy, and photoelectrochemical measurements confirm the absence of aggregation in solution and on ZnO single-crystal surfaces. At high surface coverage on the ZnO surface, individual polymer chains are resolved, and photocurrent efficiency measurements suggest that charge injection occurs with mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The strong variation across the P1-O- n series strongly suggests that the aggregation in the longer chain polymers leads to a significant reduction in the efficiency of charge injection. This correlates with earlier work we reported in collaboration with Sambur and Parkinson, where it was found that the APCE was negatively affected under conditions where aggregated polymers could be observed at a single-crystal TiO 2 interface by AFM …”
Section: Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The strong variation across the P1-O- n series strongly suggests that the aggregation in the longer chain polymers leads to a significant reduction in the efficiency of charge injection. This correlates with earlier work we reported in collaboration with Sambur and Parkinson, where it was found that the APCE was negatively affected under conditions where aggregated polymers could be observed at a single-crystal TiO 2 interface by AFM …”
Section: Results and Discussionsupporting
confidence: 92%
“…23 Furthermore, molecular dynamics study of the P2-C-n chains shows that they adopt a helical conformation rather than wormlike conformations in solution. 33 An atomic force microscopy (AFM) study of P2-C-n chains adsorbed on single-crystal (anatase) TiO 2 showed that the effective diameter of single (helical conformation) polymer chains is 47 ± 3 Å. 32 Interestingly, the size of the P2-C series in solution as monitored by DLS is consistent with the previously reported AFM-determined size for the same polymers adsorbed on TiO 2 (7 nm vs 5 nm).…”
Section: ■ Results and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A similar improvement of perovskite absorption and coverage was recently achieved by adding CH 3 NH 3 Cl to the standard CH 3 NH 3 PbI 3 precursor. 28 In the DSSC research community, alternative binary oxides such as ZnO, [29][30][31][32] SnO 2 , 33-34 Nb 2 O 5 35-37 and ternary oxides such as SrTiO 3 (STO), [38][39][40][41] BaSnO 3 , 42 and Zn 2 SnO 4 [43][44] have been explored as the electron transporter. For the perovskite photovoltaic research, only ZnO has been investigated as an alternative electron transporting layer so far, 13 and there is an urgent need to explore wide-bandgap oxides with suitable band alignments and crystal structures to improve device performance, particularly V OC .…”
mentioning
confidence: 99%